2009
DOI: 10.1038/hr.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

The association between masked hypertension and waist circumference as an obesity-related anthropometric index for metabolic syndrome: the Ohasama study

Abstract: Masked hypertension has been proven to be associated with an increased risk for cardiovascular diseases. The purpose of this study was to examine the direct associations of obesity-related anthropometric indices, including waist circumference, with masked hypertension. Participants in this population-based survey included 395 residents (> or = 35 years) of Ohasama, a rural Japanese community. They measured blood pressure at home (HBP) and underwent an oral glucose-tolerance test. Participants were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
(47 reference statements)
0
24
0
1
Order By: Relevance
“…8,11 However, only a few studies have assessed HOMA-IR in masked hypertension. [21][22][23][24] A Japanese populationbased study found only nonsignificant differences between masked hypertension, defined with home BP and the other BP groups. 21 Another study performed ambulatory BP measurement on 76 untreated, non-diabetic patients and observed significantly higher HOMA-IR in masked, white-coat and sustained hypertension than in normotension.…”
Section: Insulin Resistancementioning
confidence: 95%
See 1 more Smart Citation
“…8,11 However, only a few studies have assessed HOMA-IR in masked hypertension. [21][22][23][24] A Japanese populationbased study found only nonsignificant differences between masked hypertension, defined with home BP and the other BP groups. 21 Another study performed ambulatory BP measurement on 76 untreated, non-diabetic patients and observed significantly higher HOMA-IR in masked, white-coat and sustained hypertension than in normotension.…”
Section: Insulin Resistancementioning
confidence: 95%
“…Although patients with MS frequently have high-normal or elevated office, home and ambulatory BP levels, only a few studies have touched briefly on MS or insulin resistance in masked hypertension. 5,7,[14][15][16][17][18][19][20][21][22][23][24] Most of these studies were based on selected patient groups [14][15][16][17][18][19][20][22][23][24] and only a few of them reported the criteria used to define MS. [14][15][16] The majority of them did not find any significant differences between BP subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Results from urban Japanese men showed that waist-to-hip ratio, but not BMI, was linearly associated with HbA1c, and waist-to-hip ratio was positively associated with serum total cholesterol levels and inversely associated with HDL-cholesterol levels, even after adjusting for BMI (Iso et al 1991 ) . Similar stronger relationships between the variables associated with abdominal obesity (waist circumference and waist-to-hip ratio) and the prevalence of hypertension, diabetes, and accumulation of metabolic abnormalities have been reported in some cross-sectional studies with Japanese participants (Ito et al 2003 ;Hsieh and Muto 2005 ;Huxley et al 2008 ;Kato et al 2008 ;Nakamura et al 2008 ;Asayama et al 2009 ) . In contrast, some reports have shown that the association is similar for BMI and waist circumference (Nakamura et al 2007 ; Obesity in Asia Collaboration 2008 ; Kondo et al 2009 ) , and some reports showed that the relationship to some metabolic abnormalities was stronger for BMI than waist circumference (Sakurai et al , 2008Decoda Study Group 2008 ;Kondo et al 2009 ) .…”
Section: Gender Differences In Anthropometric Indices Refl Ecting Obementioning
confidence: 50%
“…95 Further, in the International Database in Ambulatory blood pressure in relation to Cardiovascular Outcomes showed a difficult in BP control in diabetes subjects with MHT, with worst outcomes, so the clinician may pay particular attention in BP control of this group. 96 Despite the increased adoption of HBPM and clear utility for diagnosis, as demonstrated in obese patients, 97 ABPM remain the best method to correctly assess the cardiovascular prognosis also at follow-up. 98 …”
Section: Managementmentioning
confidence: 99%